The lichen genera Aspiciliopsis, and Placopsis (Trapeliales: Trapeliaceae: Ascomycota) in New Zealand - Galloway, David J. (Phytotaxa, 2013)
Aspiciliopsis macrophthalma and 38 species of Placopsis are recognized in the New Zealand mycobiota. Placopsis campbelliana, and P. erosa are newly described. A key to species is given, together with details of synonymy and typification, descriptions of all taxa, their chemistry, distribution, ecology and biogeographical affinities. Lichenicolous fungi parasitising species of Placopsis are recorded. The importance of Placopsis as a fast-growing and active nitrogen-fixer in natural ecosystems is noted as well as the role of certain species in processes of soil consolidation and natural environmental repair processes. The utility of some species for lichenometric studies in recently deglaciated environments of the Southern Hemisphere is also noted.